A wireless remote high-power laser device for optogenetic experiments. (26th February 2015) - Wang, Y; Gong, Q; Li, Y Y; Li, A Z; Zhang, Y G; Cao, C F; Xu, H X; Cui, J; Gao, J J
Abstract: Optogenetics affords the ability to stimulate genetically targeted neurons in a relatively innocuous manner. Reliable and targetable tools have enabled versatile new classes of investigation in the study of neural systems. However, current hardware systems are generally limited to acute measurements or require external tethering of the system to the light source. Here we provide a low-cost, high-power, remotely controlled blue laser diode (LD) stimulator for the application of optogenetics in neuroscience, focusing on wearable and intelligent devices, which can be carried by monkeys, rats and any other animals under study. Compared with the conventional light emitting diode (LED) device, this LD stimulator has higher efficiency, output power, and stability. Our system is fully wirelessly controlled and suitable for experiments with a large number of animals.